KEABSAHAN JUAL BELI YANG TANDA TANGANNYA DISANGKAL OLEH PENJUAL (Studi Kasus: Putusan No.48/Pdt.g/2014/PMS) - FENDI WILLIAM (PREMISE LAW JURNAL, 2019)
Dosen pembimbing:1. Prof. Dr. Budiman Ginting, SH, MHum2. Prof. Dr. Muhammad Yamin, SH, MS, CN3. Dr. Edy Ikhsan, SH, MA The implementation of land transaction among the middle and lower class of people, either by cash or credit, is through buying and selling. Sales deed made in the office of Notary/PPAT has legal force as evidence since it is made according to law. However, the Notary takes liability for the persons appearing whose deeds are made. An authentic deed as strong evidence plays an important role in every legal case. Right and obligation which are clearly found in an authentic deed guarantees legal certainty and can avoid any dispute.The research used juridical normative which was library research with historical and legal provision approach about the liability of the persons appearing involved in making deeds in the PPAT office with witnesses who sign them.Based on the research done by the writer, he get knowledge about the power of a deed as evidence and how a PPAT who had submitted deed protocol for which the receiver of the deed protocol was involved in making the deed as evidence when the parties file complaint on PPAT’s deeds.Keywords: PPAT Deed, Evidence, the Parties’ Complaint